Implementasi Kegiatan Sholawat Wahidiyah Sebagai Pendidikan Akhlak di Kampung Lg. Banjarejo – Kalimantan Timur - Saipul Rachmat Hamdani; Muhamad Illiyin Bahar Amik (Journal of Islamic Studies & Social Science, 2024)
The purpose of this paper is to analyze a method of shalawat wahidiyah to foster and build spirituality within. This spiritual development is expected to give birth to ahlak karimah with sholawat wahidiyah approach. This activity was conducted by Saljul Qulub Junior High School, Kedunglo Miladiyah boarding school in Kediri. The method used in this research is qualitative method. The result of this research is the effort of shalawat wahidiyah activities to give birth to the realization of the people's ahlak in their daily lives.